Front-line worker perspectives on Indigenous youth suicide in Central Australia: initial treatment and response†. (2nd July 2016) - Kuipers, Pim; Lindeman, Melissa A.; Grant, Laurencia; Dingwall, Kylie
ABSTRACT: The high suicide rate of Australian Aboriginal young people prompted a Northern Territory parliamentary inquiry. In response, a project was established to develop a local data collection system for Indigenous youth suicide and suicide attempts in Central Australia, and to propose more effective referral pathways between agencies. A core component of this project was interviews with front-line workers. Secondary analysis of the 22 interview transcripts collected for the project revealed deep insights from front-line workers who deal with Aboriginal young people in a variety of local service and community settings. Key themes pertaining to initial treatment and response were identified: immediate response, follow-up services, staffing support, assessment and decision-making, community involvement and skills development. A more coordinated, client-centred approach is recommended with clearly defined communication pathways inclusive of family and local community members, sensitive to inter-agency relationships, and requiring improved skills and confidence for all involved. As far as possible, decisions about services and responses should be made locally and be informed by preferences of the local community.